Green synthesized metal nanoparticles as a selective inhibitor of human osteosarcoma and pathogenic microorganisms. (September 2019) - Francis, S.; Nair, K.M.; Paul, N.; Koshy, E.P.; Mathew, B.
Abstract: Nanobiotechnology gained at most importance in the current health-care systems. The present study reports the synthesis and characterization of silver and gold nanoparticles which in turn act as a selective inhibitor of human osteosarcoma. The in vitro anticancer studies on U2OS produced IC50 values in the therapeutic range of 29.22 ± 0.42 and 32.83 ± 0.81 μg/mL for silver and gold nanoparticles, while the fibroblast cells (L929) produced IC50 values of 141.26 ± 2.5 and 157.23 ± 2.11 μg/mL for silver and gold nanoparticles, respectively. The growth and action of infectious pathogens can be inhibited by the synthesized nanoparticles. The silver nanoparticles is used to scavenge the hydrogen peroxide and served as a sensor. The time-conserving microwave-assisted nanoparticle fabrication procedure is used here at the natural pH. Silver and gold nanoparticles have surface plasmon resonance peaks at 437 and 553 nm, respectively. The Fourier Transform Infrared spectroscopy fingerprints the role of amide groups of proteins in the synthesis and stabilization process. Transmission electron microscopic analysis proved the spherical geometry of silver and gold nanoparticles with an average size of 20.49 ± 6.68 nm and 25.05 ± 7.31 nm, respectively. Highlights: Silver and gold nanoparticles act as a selective inhibitor of human osteosarcoma. The in vitro anticancer studies on U2OS produced IC50 values in the therapeutic range. Silver nanoparticles are used to scavenge hydrogen peroxide and served as a sensor.